2006
DOI: 10.1002/art.22247
|View full text |Cite
|
Sign up to set email alerts
|

Knee joint loading differs in individuals with mild compared with moderate medial knee osteoarthritis

Abstract: Objective. To compare the knee joint loading patterns in individuals with differing radiographic grades of knee osteoarthritis (OA) for characterization of the mechanical implications of different structural states, and to compare the knee adduction angular impulse, a measure of gait complementary to the commonly used peak knee adduction moment.Methods. Asymptomatic subjects (those without knee OA) having a Kellgren/Lawrence (K/L) radiographic severity grade of 0 or 1 (n ‫؍‬ 28) and subjects with symptomatic k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
169
4
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(191 citation statements)
references
References 27 publications
12
169
4
6
Order By: Relevance
“…The EKAM has been used as a proxy for medial knee joint load, and a reduction in the EKAM represents a change in medial to lateral distribution and a relative lowering of the medial compartment load (9). The area underneath the EKAM curve, the knee adduction angular impulse (KAAI), represents the cumulative effect of the EKAM over the stance phase (10). High medial knee loading during walking estimated using the EKAM and KAAI is predictive of structural progression in knee OA (3,5,6), under the tenet that high knee loading in the presence of established disease overwhelms the normal regulation of healthy tissue, precipitating ongoing structural change (11).…”
Section: Introductionmentioning
confidence: 99%
“…The EKAM has been used as a proxy for medial knee joint load, and a reduction in the EKAM represents a change in medial to lateral distribution and a relative lowering of the medial compartment load (9). The area underneath the EKAM curve, the knee adduction angular impulse (KAAI), represents the cumulative effect of the EKAM over the stance phase (10). High medial knee loading during walking estimated using the EKAM and KAAI is predictive of structural progression in knee OA (3,5,6), under the tenet that high knee loading in the presence of established disease overwhelms the normal regulation of healthy tissue, precipitating ongoing structural change (11).…”
Section: Introductionmentioning
confidence: 99%
“…The external KAM is a reliable and valid indicator of medial knee load (11,12) and is most often quantified by evaluating the 2 peaks during stance, as well as the impulse (area under the KAM-time curve). The first and typically largest peak occurs during the load acceptance phase of gait (approximately 25% stance), and the second peak occurs during the propulsion phase (approximately 75% stance) (13)(14)(15). Clinical implications of a large KAM are significant as the peak KAM is a strong predictor of medial compartment OA radiographic disease severity (16), rate of disease progression (6), and development of chronic knee pain (17).…”
Section: Introductionmentioning
confidence: 99%
“…This shows that when arm swing range is small, the dynamic load in the frontal plane decreases. Kito 5) and others 10,11) reported that the internal knee abduction moment of patients with knee OA is larger than that of healthy individuals during the stance phase. This suggests that patients with the knee OA have a smaller arm swing range in order to avoid pain.…”
Section: Discussionmentioning
confidence: 99%